(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
In this article, the use of innovative technologies in the teaching of mother tongue, increasing interest in the use of interactive methods in the educational process, pedagogical and information technology in the teaching process, the process of teaching the mother tongue a number of current problems and shortcomings awaiting their proof in terms of formulation are described in detail.